Special Editorial Issue EJTIR - Haan, Alexander R.C. de; Riet, Odette A.W.T. van de (European Journal of Transport and Infrastructure Research, 2010)
Globalisation and economic growth have led to aviation’s deep incorporation into our society. People and goods can be transported almost anywhere on the globe in a relatively short time and at relatively low prices. The rate of growth in air traffic demand has for decades been higher than that of the world economy. As world population increases, economic growth and ongoing globalisation are expected to continue fuelling air traffic’s explosive growth (Walker et al, 2008). As a result the large aircraft manufacturers in the world, Airbus and Boeing, specify in their market forecast annual growth percentages of around 5 to 6%. Since late 2008, the economic crisis has significantly reduced the demand for aviation (IATA, 2008; 2009). However, most authors consider this slowdown to be but temporary. In many occasions in the past, aviation demand growth curbed but growth figures always relatively quickly recovered picking up the growth lines followed before the crisis. The latest occasion has been the recovery in 2004 from the period of stagnation following the attacks on the World Trade Centre in New York City in 2001. In the majority of designed future scenarios for air traffic, the increasing demand for air traffic is expected to continue. This continuing growth will have some valuable effects, but also some drawbacks.